A VTI anisotropic media inversion method based on the exact reflection coefficient equation - Wu, Fan; Li, Jingye; Geng, Weiheng; Tang, Wei (Frontiers in Physics, 2022)
Anisotropy is widespread in the Earth's crust, and VTI (vertical axis symmetry transverse isotropy) anisotropy is common due to the stratigraphic pressure. Disregarding anisotropy leads to inaccurate inversion results in VTI media. To estimate accurate elastic parameters, the exact reflection coefficient equation on VTI media should be used. The exact reflection coefficient equation is nonlinear and more accurate than the commonly used linear reflection coefficient equation. Although the inversion based on the VTI anisotropy exact reflection coefficient equation is a complex nonlinear inversion problem. But it is still computable. Therefore, for VTI media, we derive the objective function combining Bayesian theory and use the iterative reweighted least squares method for fast and stable solution. Adding Bayesian theory can improve the robustness of the algorithm. The accuracy and noise immunity of the method is tested with synthetic data. Finally, the method is applied on field data and obtain accurate elastic parameters. The results can provide an understanding of subsurface formations and serves as the base data for calculating fluid and fracture distribution.